Assessing users satisfaction with web digital library: the case of Universiti Teknologi MARA. Issue 1 (4th January 2016) - Masrek, Mohamad Noorman; Gaskin, James Eric
Abstract : Purpose: – The purpose of this paper is to examine the determinants of user satisfaction in the context of academic web digital library (DL). A model based on the re-specified information system success model was developed and tested using the structural equation modeling (SEM) technique. Design/methodology/approach: – The study employed survey research methodology with self-administered questionnaire as the research instrument. The questionnaire was developed based on the instruments used by previous researchers. The population of the study was students enrolled for the bachelor's degree in the Faculty of Information Management, Universiti Teknologi MARA, Malaysia. These students were chosen because of researcher's easy access to the sampling frame. Descriptive analysis and inferential analysis which include SEM were executed using IBM SPSS and AMOS statistical software. Findings: – The findings indicate that information quality, systems quality, service quality, perceived usefulness, perceived ease of use and cognitive absorption are significant predictor of users' satisfaction with the web DL. Research limitations/implications: – Instead of collecting data from students from various faculties, this study only covered students enrolled in one faculty. In the same light, as the respondents were from one faculty, they only report their experience of using one DL. Given these limitations, the results obtained are narrowed in terms of generalizability. The second limitation of the study is related to the predictor variables which only focussed on six variables only. Practical implications: – From the practical viewpoint, the instrument that has been developed can be used as a diagnostic tool for continuous improvements of the DL. Originality/value: – From the theoretical viewpoint, the study has developed an empirical based framework that depicts critical factors influencing DL satisfaction. Researchers specializing on the assessment of DL effectiveness can consider adopting the framework for future studies. Alternatively, the framework can be further extended by integrating other variables such as users' characteristics or organizational characteristics.